Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

We have to evaluate the following:

$$1^2 \cdot 2! + 2^2 \cdot 3! + \cdots + n^2 \cdot (n+1)! =\sum_{k=1}^{n} k^2 \cdot (k+1)!$$

Any hints ?

share|improve this question
2  
The result should be $2 - (n+2)! + n(n+2)!$. You can show this by induction, although I'm not sure how you can derive this result. –  George V. Williams Mar 19 '13 at 0:53
    
Sounds a lot like homework. If so, tag it so. –  Rick Decker Mar 19 '13 at 1:32
    
Not a homework... –  Vishwesh Mar 19 '13 at 1:48
add comment

3 Answers

up vote 8 down vote accepted

Let

$$f_k = (k-1) (k+2)!$$

Then

$$f_k-f_{k-1} = k^2 (k+1)!$$

and

$$\begin{align}\sum_{k=1}^n k^2 (k+1)! &= f_1 - f_0 + f_2 - f_1 + \ldots+f_{n}-f_{n-1}\\ &= f_n-f_0\\ &= (n-1)(n+2)! + 2\end{align}$$

ADDENDUM

How did I get my $f_k$? By assuming that such an anti-difference takes the form

$$f_k = (k+m) (k+n)!$$

This general form will produce a quadratic times some factorial upon differencing. Here

$$f_k - f_{k-1} = [(k^2-(m+n-1) k + m (n-1) + 1] (k+n-1)!$$

We want to isolate a factor of $k^2$ in the brackets. Then we have to solve

$$m+n-1=0$$ $$m (n-1) + 1=0$$

The solutions are $(m,n) = (-1,2)$ and $(1,0)$. The former solution provides the form we seek.

share|improve this answer
2  
It would be good to comment on how to obtain the "discrete primitive" $f_k$ in this case. –  Pedro Tamaroff Mar 19 '13 at 1:44
    
Thanks a lot @Ron Gordon –  Vishwesh Mar 19 '13 at 1:49
    
@PeterTamaroff: I hate to say it, but it was just a lot of messing around until I got the $f_k$ whose difference was the term being summed. I am not aware of a general method by which one finds an "anti-difference." –  Ron Gordon Mar 19 '13 at 2:03
    
@RonGordon See Sasha's answer. –  Did Mar 19 '13 at 8:00
    
@Did: I did, and from my perspective, it has just as much deux ex machina as mine. –  Ron Gordon Mar 19 '13 at 8:02
show 6 more comments

Using $k^2 = (k+3)(k+2) - 5 (k+2) + 4$ we write $$f_k = k^2 (k+1)! = (k+3)! - 5 (k+2)! + 4 (k+1)! = G_{k+1} - G_k$$ where $G_k = (k+2)! - 4(k+1)!$, therefore $$ \sum_{k=1}^n f_k = \sum_{k=1}^n \left(G_{k+1} - G_k\right) = G_{n+1} - G_1 $$ Since $G_1 = -2$, and $G_{n+1} = (n+3)! - 4(n+2)! = (n+2)! (n-1)$ we get $$ \sum_{k=1}^n k^2 (k+1)! = (n-1) (n+2)! + 2 $$

share|improve this answer
add comment

Using k2=(k+3)(k+2)−5(k+2)+4 we write fk=k2(k+1)!=(k+3)!−5(k+2)!+4(k+1)!=Gk+1−Gk where Gk=(k+2)!−4(k+1)!, therefore ∑k=1nfk=∑k=1n(Gk+1−Gk)=Gn+1−G1 Since G1=−2, and Gn+1=(n+3)!−4(n+2)!=(n+2)!(n−1) we get ∑k=1nk2(k+1)!=(n−1)(n+2)!+2

share|improve this answer
2  
Please use $\LaTeX$ when typesetting math. Use this guide: meta.math.stackexchange.com/questions/5020/… –  Dennis Gulko Mar 19 '13 at 8:17
    
This appears to be a duplicate of Sasha's solution, non-LaTeX'ed, but character-for-character. –  Ron Gordon Mar 19 '13 at 13:28
    
Please do not plagiarize. This can lead to suspension. –  robjohn Mar 19 '13 at 18:05
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.